The redefinition of home birth in the practice of obstetric nurses (Research, Society and Development, 2020)
Introduction: Brazil has currently shown a behavior of opposition to women and health professionals who choose the domestic environment as a suitable place to give birth. Objective: To understand the resignification of home birth in the practice of obstetric nurses. Method: Field research type study, of a descriptive nature with a qualitative approach, whose reflections and perceptions were collected through an instrument of the type semi-structured interviews, with the previous elaboration of a questionnaire. The content analysis proposed by Bardin was used, which in turn supported the construction of four categories: care rituals: preparation for childbirth; paradigm break: a process of change; restoration of the power of the female body and obstetric nurses, giving a new meaning to home birth in care practice. Conclusion: Home birth rescues an old culture, under a new perspective of empowerment of the couple and family, providing them with a respectful and safe delivery.